Estimation of increased pulmonary wedge pressure by an algorithm based on noninvasively measured pulmonary diastolic pressure in cardiac patients independent of left ventricular ejection fraction. Issue 2 (15th February 2020) - Barbier, Paolo; Cucco, Cuono; Guglielmo, Marco; Simioniuc, Anca; Fabiani, Iacopo; Pugliese, Nicola Riccardo; Savioli, Gabriele; Dini, Frank Lloyd
Abstract: Aim: Pulmonary artery diastolic pressure (PADP) correlates closely with pulmonary wedge pressure (PAWP); therefore, we sought to evaluate whether an algorithm based on PADP assessment by the Doppler pulmonary regurgitation (PR) end‐diastolic gradient (PRG) may aid in estimating increased PAWP in cardiac patients with reduced or preserved left ventricular (LV) ejection fraction (EF). Methods and Results: Right heart catheterization, with estimation of PAWP, right atrial pressure (RAP), PADP, and Doppler echocardiography, was carried out in 183 patients with coronary artery disease (n = 63), dilated cardiomyopathy (n = 52), or aortic stenosis (n = 68). One‐hundred and seventeen patients had LV EF <50%. We measured the pressure gradients across the tricuspid and pulmonary valves from tricuspid regurgitation (TRV) and PR velocities. Doppler‐estimated PADP (e‐PADP) was obtained by adding the estimated RAP to PRG. An algorithm based on e‐PADP to predict PAWP, that included TRV, left atrial volume index, and mitral E/A, was developed and validated in derivation (n = 90) and validation (n = 93) subgroups. Both invasive PADP ( r  = .92, P  < .001) and e‐PADP ( r  = .72, P  < .001) correlated closely with PAWP, and e‐PADP predicted PAWP (AUC: 0.85, CI: 0.79‐0.91) with a 94% positive predictive value (PPV) and a 55% negative predictive value (NPV), after exclusion of five patients with precapillary pulmonary hypertension. The e‐PADP‐based algorithm predicted PAWP with higher accuracy (PPV = 94%; NPV = 67%; accuracy = 85%; kappa: 0.65, P  < .001) than the ASE‐EACVI 2016 recommendations (PPV = 97%; NPV = 47%; accuracy = 68% undetermined = 18.9%; kappa: 0.15, P  < .001). Conclusions: An algorithm based on noninvasively e‐PADP can accurately predict increased PAWP in patients with cardiac disease and reduced or preserved LV EF.